Sawdust-based carbon dot and preparation method of luminous film of sawdust-based carbon dot

By using wood chips as the carbon source and combining with the hydrothermal process, the problems of uneven particle size and limited luminescence range of biomass carbon dots were solved, and the preparation of carbon dots with high transparency and excellent luminescence properties was achieved, expanding its high-end application fields. potential.

CN119351091AActive Publication Date: 2025-01-24CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411474008.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing carbon dots prepared based on biomass have problems of uneven particle size and limited luminescence range, which limits their promotion in high-end application fields.

Method used

Wood chips are used as the initial carbon source, and biomass carbon quantum dots are prepared by water thermal method to optimize process parameters to improve particle size uniformity and luminous performance.

Benefits of technology

Preparation of carbon points with uniform particle size and excellent luminous performance, improved the transparency and luminous performance of the luminous film, and expanded its application prospects in the fields of optical devices and display technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351091A_ABST
    Figure CN119351091A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sawdust-based carbon dot, explores the luminescence property of the carbon dot and the application of the carbon dot in the optical field, and also discloses a preparation method of a sawdust-based carbon dot luminescent film. The preparation method comprises the following steps: preparation of carbon dots: wood chips are soaked in a sodium hypochlorite solution, centrifugal treatment is performed after a sealed stirring reaction, lower-layer jelly is taken and washed repeatedly, and freeze-drying treatment is performed to obtain freeze-dried cellulose; the preparation method comprises the following steps: soaking freeze-dried cellulose in deionized water, fully crushing to obtain a solid-liquid mixture, pouring the solid-liquid mixture into a polytetrafluoroethylene lining, and carrying out hydrothermal reaction in a vacuum drying oven; centrifuging after the reaction is completed, dialyzing the obtained supernate, and freeze-drying to obtain the carbon dots. And preparation of the carbon dot-based thin film: dissolving the obtained carbon dot solid into a carbon dot solution, obtaining a mixed solution by adopting a PVA film forming method, fully crushing, and drying to obtain the carbon dot-based thin film. Through exploration, when the concentration of the carbon dots reaches 30%, the peak value of the fluorescence emission peak of the film appears at 472 nm, cyan light exists, and the position of the emission peak continues to generate red shift along with the increase of the concentration of the CDs, which proves that the light-emitting films with different carbon dot concentrations have the same properties of absorbing short wavelength light and converting the short wavelength light into longer wavelength emission as a CDs aqueous solution. The preparation method not only can complete industrial waste recycling, is green and environment-friendly, but also conforms to the current carbon neutralization concept in China.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials, in particular to a method for preparing sawdust-based carbon dots and luminescent films thereof. Background Art

[0002] As a new type of zero-dimensional nanomaterial, carbon dots (CDs) have become the representative of the new generation of photoluminescent materials due to their advantages such as simple preparation, abundant raw materials, low price, adjustable emission, good optical stability and good biocompatibility. Among the many raw materials that can be used to prepare CDs, biomass has attracted much attention due to its advantages such as green environmental protection and sustainability. As a biomass resource with large reserves and wide applications, wood has significant advantages in the preparation of CDs. The preparation process of carbon quantum dots is simple, and it has the advantages of high yield, low cost and environmental friendliness. In addition, due to its small size, good biocompatibility, high chemical stability, adjustable hydrophilicity, rich surface functional groups and strong anti-pollution ability, it has broad application prospects in the field of luminescent functional materials.

[0003] In recent years, the idea of ​​green chemistry has been gradually integrated into the synthesis process of carbon quantum dots. Biomass resources have many advantages such as low cost, renewable, high carbon content, and easy preparation. They have been widely used as carbon source precursors in the preparation of biomass-based carbon quantum dots. However, the carbon dots prepared based on biomass currently have problems such as uneven particle size and limited luminescence range, which limits their promotion in high-end application fields.

[0004] Therefore, it is of great research significance and application value to develop an efficient and environmentally friendly method for preparing carbon dots based on sawdust and to prepare thin films with high transparency and excellent luminescence properties. Summary of the invention

[0005] The present invention aims to provide a method for preparing sawdust-based carbon dots and luminescent films thereof, so as to solve the problems of uneven particle size and limited luminescent range of biomass carbon dots in the prior art, and improve the transparency and luminescent performance of the film. The method uses sawdust as the initial carbon source, processes the sawdust to obtain cellulose, and attempts to prepare biomass carbon quantum dots by a hydrothermal method. The use of sawdust as raw material to prepare carbon dots can not only complete the recycling of industrial waste, be green and environmentally friendly, but also conform to my country's current carbon neutrality concept. It has broad application prospects in biosensing, bioimaging, drug delivery, photovoltaic devices, and optoelectronic device preparation.

[0006] The present invention provides a method for preparing sawdust-based carbon dots and luminescent films thereof, comprising the following steps: (1) Using sawdust as raw material, completely immerse it in a sodium hypochlorite solution, seal it with plastic wrap, and stir it on a magnetic stirrer until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1), taking out the lower layer of colloid, and rinsing it in deionized water, centrifuging the mixture again, taking out the lower layer of colloid, and rinsing it in deionized water three times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2), and then vacuum drying to obtain freeze-dried cellulose, dividing the freeze-dried cellulose into small pieces, soaking them in deionized water, and using an ultrasonic cell crusher to break up the resulting solid-liquid mixture until the freeze-dried cellulose is completely broken to form a milky white suspension; (4) stirring the milky white suspension obtained in step (3), pouring it into a polytetrafluoroethylene liner, placing it into a high-pressure reactor, reacting it in a vacuum drying oven using a hydrothermal method, and taking it out after the reactor is cooled; (5) Centrifuging the solid-liquid mixture obtained in step (4), taking out the supernatant and filtering it, and freeze-drying the filtrate to obtain a viscous solid. Then dissolving the viscous solid in water, and repeatedly centrifuging and filtering it several times to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) adding polyvinyl alcohol solid particles into deionized water, stirring and heating until completely dissolved, and then cooling to room temperature to obtain a polyvinyl alcohol (PVA) solution; (7) Dissolving the carbon dot solid obtained in step (5) in deionized water to obtain a carbon dot solution, mixing the carbon dot solution with the polyvinyl alcohol solution obtained in step (6), adding the polyvinyl alcohol solution to the mixed solution until the total volume of the mixed solution is 20 ml, treating the mixed solution with an ultrasonic cell crusher, and then drying the mixed solution in a vacuum drying oven to obtain a light brown luminescent film.

[0007] Preferably, in step (1), the mass of sawdust weighed is 9 g, the concentration of the sodium hypochlorite solution is 4.8 wt %, 200 ml of the sodium hypochlorite solution is weighed, and the stirring time of the magnetic stirrer is about 60 min.

[0008] Preferably, in step (2), the centrifugal speed of the centrifuge is 10000 r / min, and the centrifugal time is 5 min.

[0009] Preferably, in step (3), the freeze-drying time is about 4 hours, the vacuum drying time is about 20 hours, the freeze-dried cellulose mass is weighed to be 0.171 g, 60 ml of deionized water is weighed, the power of the ultrasonic cell crusher is set to 45%, the operation is 1.5 seconds, and the interval is 2 seconds.

[0010] Preferably, in step (4), the speed of the magnetic stirrer can be controlled below 300 r / min, 100 ml of the polytetrafluoroethylene liner is taken, and the temperature in the vacuum drying oven is adjusted to 200° C. for 720 min.

[0011] Preferably, in step (5), the centrifugal speed of the centrifuge is 10000 r / min, the centrifugal time is 5 min, and a 0.22 μm microfiltration membrane is used for filtration.

[0012] Preferably, in step (6), 40 g of polyvinyl alcohol solid particles are weighed, 460 ml of deionized water is weighed, the stirring speed of the thermomagnetic stirrer is 200 r / min, and the heating temperature does not exceed 80°C.

[0013] Preferably, in step (7), the mass volume ratio of carbon dot solid and deionized water is 5:1, the concentration of the polyvinyl alcohol solution is 8wt%, the polyvinyl alcohol is selected as 1788 low-viscosity type, the degree of alcoholysis is 87.0-89.0%, the power of the ultrasonic cell crusher is set to 45%, the operation is 1.5s, the interval is 2s, and the duration is 3min. The temperature of the vacuum drying oven is adjusted to 60°C, and the vacuum drying time is about 7h.

[0014] The present invention also provides a luminescent film prepared by the aforementioned method for preparing the sawdust-based carbon dots and luminescent film.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] 1. The present invention uses sawdust as a carbon source, realizes the effective utilization of biomass resources, and conforms to the concepts of green environmental protection and sustainable development. 2. The present invention prepares carbon dots with uniform particle size and excellent luminescence performance by optimizing the hydrothermal process parameters, thus solving the problems of uneven particle size and limited luminescence range of biomass carbon dots in the prior art. 3. The luminescent film prepared by the present invention has good transparency and excellent luminescent performance, and can be widely used in optical devices, display technology, anti-counterfeiting materials and other fields, and has broad market prospects and application value.

[0017] The above content is an overview of the technical solution. The present invention will be further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to clearly illustrate the technical solutions for implementing the present invention, the implementation process and the drawings required for use in the embodiments are briefly introduced below. The following drawings only show some embodiments of the present invention and therefore should not be regarded as limiting the present invention in any form. Figure 1 This is an optical photograph of the dry luminescent film prepared by the present invention; Figure 2 The fluorescence emission spectra (PL) of the CDs solution prepared by the present invention at different excitation wavelengths; Figure 3The fluorescence emission spectra (PL) of the luminescent films with different concentrations of CDs (4.5-30% CDs) prepared by the present invention under the excitation of 365nm wavelength; Figure 4 It is the CIE (1931) coordinate diagram of CDs luminescent film (4.5–30% CDs) under 365nm wavelength excitation; Figure 5 These are pictures of 4.5% concentration CDs film and 30% concentration CDs film observed under 365nm ultraviolet light. DETAILED DESCRIPTION In order to better understand the technical content of the present invention, the technical solution of the present invention is further described below in conjunction with specific embodiments and drawings. It should be understood that the embodiments of the present invention are only used to illustrate the present invention and are not intended to limit the present invention in any form. Example 1 A method for preparing sawdust-based carbon dots and luminescent films thereof comprises the following steps: (1) Weigh 9 g of sawdust and 200 ml of sodium hypochlorite solution, immerse the sawdust completely in the 4.8 wt % sodium hypochlorite solution, seal with plastic wrap, pierce holes in the plastic wrap to prevent excessive reaction, and stir on a magnetic stirrer for about 60 min until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1) at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water; centrifuging the mixture again at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water for 3 times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2) for about 4 hours, and then vacuum drying for about 20 hours to obtain freeze-dried cellulose; weighing 0.171 g of freeze-dried cellulose and dividing it into small pieces, soaking it in 60 ml of deionized water, and using an ultrasonic cell crusher to crush the resulting solid-liquid mixture. The power of the ultrasonic cell crusher was set to 45%, and the operation was performed for 1.5 seconds with an interval of 2 seconds until the freeze-dried cellulose was completely crushed to form a milky white suspension; (4) Stir the milky white suspension obtained in step (3) on a magnetic stirrer at a speed of less than 300 r / min, then pour it into a 100 ml polytetrafluoroethylene liner, put it into a high-pressure reactor, and react it in a vacuum drying oven using a hydrothermal method. The temperature in the vacuum drying oven is adjusted to 200° C. for 720 min, and the reactor is taken out after cooling down; (5) The solid-liquid mixture obtained in step (4) was centrifuged at a centrifugal speed of 10,000 r / min for 5 min, the supernatant was taken out and filtered with a 0.22 μm microfiltration membrane, and the filtrate was freeze-dried to obtain a viscous solid. The viscous solid was then dissolved in water and centrifuged and filtered repeatedly to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) Weigh 40 g of polyvinyl alcohol solid particles, divide them into eight portions, 5 g each, add them into 460 ml of deionized water in batches, stir them thoroughly and heat them to 80° C. on a hot stirrer at a speed of 200 r / min until they are completely dissolved, and then cool them to room temperature to obtain an 8 wt % polyvinyl alcohol (PVA) solution; (7) Weigh 170 mg of the carbon dot solid obtained in step (5), dissolve it in deionized water at a ratio of 5 mg / mL to obtain 34 ml of carbon dot solution, use a pipette to draw 0.9 ml of the carbon dot solution and place it in a beaker, then use a measuring cylinder to weigh the 8 wt% polyvinyl alcohol solution obtained in step (6), add polyvinyl alcohol to the beaker and mix it with the carbon quantum dot solution until the total solution volume reaches 20 mL, at which time the carbon dot concentration in the mixed solution is 4.5% wt. Use an ultrasonic cell crusher for treatment, the ultrasonic cell crusher power is set to 45%, work for 1.5 seconds, interval 2 seconds, continue for 3 minutes, and then dry in a 60°C vacuum drying oven for about 7 hours to obtain a light brown luminescent film. After testing, the fluorescence emission spectra of the luminescent film prepared in this embodiment at different excitation wavelengths are as follows: Figure 2 shown. Figure 3 The fluorescence emission spectrum of the luminescent film of Example 1 under excitation at a wavelength of 365 nm is shown. Figure 4 The CIE chromaticity diagram of Example 1 is shown, and its coordinates are (0.2030.244). Example 2 A method for preparing sawdust-based carbon dots and luminescent films thereof comprises the following steps: (1) Weigh 9 g of sawdust and 200 ml of sodium hypochlorite solution, immerse the sawdust completely in the 4.8 wt % sodium hypochlorite solution, seal with plastic wrap, pierce holes in the plastic wrap to prevent excessive reaction, and stir on a magnetic stirrer for about 60 min until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1) at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water; centrifuging the mixture again at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water for 3 times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2) for about 4 hours, and then vacuum drying for about 20 hours to obtain freeze-dried cellulose; weighing 0.171 g of freeze-dried cellulose and dividing it into small pieces, soaking it in 60 ml of deionized water, and using an ultrasonic cell crusher to crush the resulting solid-liquid mixture. The power of the ultrasonic cell crusher was set to 45%, and the operation was performed for 1.5 seconds with an interval of 2 seconds until the freeze-dried cellulose was completely crushed to form a milky white suspension; (4) Stir the milky white suspension obtained in step (3) on a magnetic stirrer at a speed of less than 300 r / min, then pour it into a 100 ml polytetrafluoroethylene liner, put it into a high-pressure reactor, and react it in a vacuum drying oven using a hydrothermal method. The temperature in the vacuum drying oven is adjusted to 200° C. for 720 min, and the reactor is taken out after cooling down; (5) The solid-liquid mixture obtained in step (4) was centrifuged at a centrifugal speed of 10,000 r / min for 5 min, the supernatant was taken out and filtered with a 0.22 μm microfiltration membrane, and the filtrate was freeze-dried to obtain a viscous solid. The viscous solid was then dissolved in water and centrifuged and filtered repeatedly to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) Weigh 40 g of polyvinyl alcohol solid particles, divide them into eight portions, 5 g each, add them into 460 ml of deionized water in batches, stir them thoroughly and heat them to 80° C. on a hot stirrer at a speed of 200 r / min until they are completely dissolved, and then cool them to room temperature to obtain an 8 wt % polyvinyl alcohol (PVA) solution; (7) Weigh 170 mg of the carbon dot solid obtained in step (5), dissolve it in deionized water at a ratio of 5 mg / mL to obtain 34 ml of carbon dot solution, use a pipette to draw 1.5 ml of the carbon dot solution and place it in a beaker, then use a measuring cylinder to weigh the 8 wt% polyvinyl alcohol solution obtained in step (6), add polyvinyl alcohol to the beaker and mix it with the carbon quantum dot solution until the total solution volume reaches 20 mL, at which time the carbon dot concentration in the mixed solution is 7.5% wt. Use an ultrasonic cell crusher for treatment, the ultrasonic cell crusher power is set to 45%, work for 1.5 seconds, interval 2 seconds, continue for 3 minutes, and then dry in a 60°C vacuum drying oven for about 7 hours to obtain a light brown luminescent film. After testing, the fluorescence emission spectra of the luminescent film prepared in this embodiment at different excitation wavelengths are as follows: Figure 2 shown. Figure 3 The fluorescence emission spectrum of the luminescent film of Example 2 under excitation at a wavelength of 365 nm is shown. Figure 4 The CIE chromaticity diagram of Example 2 is shown, and its coordinates are (0.2040.238). Example 3 A method for preparing sawdust-based carbon dots and luminescent films thereof comprises the following steps: (1) Weigh 9 g of sawdust and 200 ml of sodium hypochlorite solution, immerse the sawdust completely in the 4.8 wt % sodium hypochlorite solution, seal with plastic wrap, pierce holes in the plastic wrap to prevent excessive reaction, and stir on a magnetic stirrer for about 60 min until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1) at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water; centrifuging the mixture again at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water for 3 times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2) for about 4 hours, and then vacuum drying for about 20 hours to obtain freeze-dried cellulose; weighing 0.171 g of freeze-dried cellulose and dividing it into small pieces, soaking it in 60 ml of deionized water, and using an ultrasonic cell crusher to crush the resulting solid-liquid mixture. The power of the ultrasonic cell crusher was set to 45%, and the operation was performed for 1.5 seconds with an interval of 2 seconds until the freeze-dried cellulose was completely crushed to form a milky white suspension; (4) Stir the milky white suspension obtained in step (3) on a magnetic stirrer at a speed of less than 300 r / min, then pour it into a 100 ml polytetrafluoroethylene liner, put it into a high-pressure reactor, and react it in a vacuum drying oven using a hydrothermal method. The temperature in the vacuum drying oven is adjusted to 200° C. for 720 min, and the reactor is taken out after cooling down; (5) The solid-liquid mixture obtained in step (4) was centrifuged at a centrifugal speed of 10,000 r / min for 5 min, the supernatant was taken out and filtered with a 0.22 μm microfiltration membrane, and the filtrate was freeze-dried to obtain a viscous solid. The viscous solid was then dissolved in water and centrifuged and filtered repeatedly to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) Weigh 40 g of polyvinyl alcohol solid particles, divide them into eight portions, 5 g each, add them into 460 ml of deionized water in batches, stir them thoroughly and heat them to 80° C. on a hot stirrer at a speed of 200 r / min until they are completely dissolved, and then cool them to room temperature to obtain an 8 wt % polyvinyl alcohol (PVA) solution; (7) Weigh 170 mg of the carbon dot solid obtained in step (5), dissolve it in deionized water at a ratio of 5 mg / mL to obtain 34 ml of carbon dot solution, use a pipette to draw 1.8 ml of the carbon dot solution and place it in a beaker, then use a measuring cylinder to weigh the 8 wt% polyvinyl alcohol solution obtained in step (6), add polyvinyl alcohol to the beaker and mix it with the carbon quantum dot solution until the total solution volume reaches 20 mL, at which time the carbon dot concentration in the mixed solution is 9% wt. Use an ultrasonic cell crusher for treatment, the ultrasonic cell crusher power is set to 45%, work for 1.5 seconds, interval 2 seconds, continue for 3 minutes, and then dry in a 60°C vacuum drying oven for about 7 hours to obtain a light brown luminescent film. After testing, the fluorescence emission spectra of the luminescent film prepared in this embodiment at different excitation wavelengths are as follows: Figure 2 shown. Figure 3 The fluorescence emission spectrum of the luminescent film of Example 3 under excitation at a wavelength of 365 nm is shown. Figure 4 The CIE chromaticity diagram of Example 3 is shown, and its coordinates are (0.2100.246). Example 4 A method for preparing sawdust-based carbon dots and luminescent films thereof comprises the following steps: (1) Weigh 9 g of sawdust and 200 ml of sodium hypochlorite solution, immerse the sawdust completely in the 4.8 wt % sodium hypochlorite solution, seal with plastic wrap, pierce holes in the plastic wrap to prevent excessive reaction, and stir on a magnetic stirrer for about 60 min until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1) at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water; centrifuging the mixture again at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water for 3 times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2) for about 4 hours, and then vacuum drying for about 20 hours to obtain freeze-dried cellulose; weighing 0.171 g of freeze-dried cellulose and dividing it into small pieces, soaking it in 60 ml of deionized water, and using an ultrasonic cell crusher to crush the resulting solid-liquid mixture. The power of the ultrasonic cell crusher was set to 45%, and the operation was performed for 1.5 seconds with an interval of 2 seconds until the freeze-dried cellulose was completely crushed to form a milky white suspension; (4) Stir the milky white suspension obtained in step (3) on a magnetic stirrer at a speed of less than 300 r / min, then pour it into a 100 ml polytetrafluoroethylene liner, put it into a high-pressure reactor, and react it in a vacuum drying oven using a hydrothermal method. The temperature in the vacuum drying oven is adjusted to 200° C. for 720 min, and the reactor is taken out after cooling down; (5) The solid-liquid mixture obtained in step (4) was centrifuged at a centrifugal speed of 10,000 r / min for 5 min, the supernatant was taken out and filtered with a 0.22 μm microfiltration membrane, and the filtrate was freeze-dried to obtain a viscous solid. The viscous solid was then dissolved in water and centrifuged and filtered repeatedly to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) Weigh 40 g of polyvinyl alcohol solid particles, divide them into eight portions, 5 g each, add them into 460 ml of deionized water in batches, stir them thoroughly and heat them to 80° C. on a hot stirrer at a speed of 200 r / min until they are completely dissolved, and then cool them to room temperature to obtain an 8 wt % polyvinyl alcohol (PVA) solution; (7) Weigh 170 mg of the carbon dot solid obtained in step (5), dissolve it in deionized water at a ratio of 5 mg / mL to obtain 34 ml of carbon dot solution, use a pipette to draw 4 ml of the carbon dot solution and place it in a beaker, then use a measuring cylinder to weigh the 8 wt% polyvinyl alcohol solution obtained in step (6), add polyvinyl alcohol to the beaker and mix it with the carbon quantum dot solution until the total solution volume reaches 20 mL, at which time the carbon dot concentration in the mixed solution is 20% wt. Use an ultrasonic cell crusher for treatment, the ultrasonic cell crusher power is set to 45%, work for 1.5 seconds, interval 2 seconds, continue for 3 minutes, and then dry in a 60°C vacuum drying oven for about 7 hours to obtain a light brown luminescent film. After testing, the fluorescence emission spectra of the luminescent film prepared in this embodiment at different excitation wavelengths are as follows: Figure 2 shown. Figure 3 The fluorescence emission spectrum of the luminescent film of Example 4 under excitation at a wavelength of 365 nm is shown. Figure 4 The CIE chromaticity diagram of Example 4 is shown, and its coordinates are (0.2210.269). Example 5 A method for preparing sawdust-based carbon dots and luminescent films thereof comprises the following steps: (1) Weigh 9 g of sawdust and 200 ml of sodium hypochlorite solution, immerse the sawdust completely in the 4.8 wt % sodium hypochlorite solution, seal with plastic wrap, pierce holes in the plastic wrap to prevent excessive reaction, and stir on a magnetic stirrer for about 60 min until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1) at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water; centrifuging the mixture again at a centrifugal speed of 10,000 r / min for 5 minutes, taking out the lower layer of colloid, and rinsing it in deionized water for 3 times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2) for about 4 hours, and then vacuum drying for about 20 hours to obtain freeze-dried cellulose; weighing 0.171 g of freeze-dried cellulose and dividing it into small pieces, soaking it in 60 ml of deionized water, and using an ultrasonic cell crusher to crush the resulting solid-liquid mixture. The power of the ultrasonic cell crusher was set to 45%, and the operation was performed for 1.5 seconds with an interval of 2 seconds until the freeze-dried cellulose was completely crushed to form a milky white suspension; (4) Stir the milky white suspension obtained in step (3) on a magnetic stirrer at a speed of less than 300 r / min, then pour it into a 100 ml polytetrafluoroethylene liner, put it into a high-pressure reactor, and react it in a vacuum drying oven using a hydrothermal method. The temperature in the vacuum drying oven is adjusted to 200° C. for 720 min, and the reactor is taken out after cooling down; (5) The solid-liquid mixture obtained in step (4) was centrifuged at a centrifugal speed of 10,000 r / min for 5 min, the supernatant was taken out and filtered with a 0.22 μm microfiltration membrane, and the filtrate was freeze-dried to obtain a viscous solid. The viscous solid was then dissolved in water and centrifuged and filtered repeatedly to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) Weigh 40 g of polyvinyl alcohol solid particles, divide them into eight portions, 5 g each, add them into 460 ml of deionized water in batches, stir them thoroughly and heat them to 80° C. on a hot stirrer at a speed of 200 r / min until they are completely dissolved, and then cool them to room temperature to obtain an 8 wt % polyvinyl alcohol (PVA) solution; (7) Weigh 170 mg of the carbon dot solid obtained in step (5), dissolve it in deionized water at a ratio of 5 mg / mL to obtain 34 ml of carbon dot solution, use a pipette to draw 6 ml of the carbon dot solution and place it in a beaker, then use a measuring cylinder to weigh the 8 wt% polyvinyl alcohol solution obtained in step (6), add polyvinyl alcohol to the beaker and mix it with the carbon quantum dot solution until the total solution volume reaches 20 mL, at which time the carbon dot concentration in the mixed solution is 30% wt. Use an ultrasonic cell crusher for treatment, the ultrasonic cell crusher power is set to 45%, work for 1.5 seconds, interval 2 seconds, continue for 3 minutes, and then dry in a 60°C vacuum drying oven for about 7 hours to obtain a light brown luminescent film. After testing, the fluorescence emission spectra of the luminescent film prepared in this embodiment at different excitation wavelengths are as follows: Figure 2 shown. Figure 3 The fluorescence emission spectrum of the luminescent film of Example 5 under excitation at a wavelength of 365 nm is shown. Figure 4 The CIE chromaticity diagram of Example 5 is shown, and its coordinates are (0.2290.281). Figure 5The images of 4.5% and 30% CDs films observed under 365nm ultraviolet light are shown. The 30% CDs carbon dot film on the left is more cyan than the 4.5% CDs film on the right. However, in the preparation of optical materials, the W-LED prepared by this route always has a cyan gap in the 470-510nm region of its emission spectrum, resulting in a trend different from sunlight, which hinders its widespread application in general lighting with high color quality. In this experiment, when the CDs concentration is 30%, the peak value of the film's fluorescence emission has already appeared at 472nm, and there is cyan light. If the carbon dot concentration continues to increase, the peak value of the film's fluorescence emission may continue to redshift, which provides ideas for preparing W-LEDs with cyan light gaps in the 470-510nm region of the emission spectrum. Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made on the basis of the present invention. Therefore, these modifications or improvements made on the basis of not departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for preparing sawdust-based carbon dots and luminescent films thereof, characterized in that: The steps include: (1) Using sawdust as raw material, completely immerse it in a sodium hypochlorite solution, seal it with plastic wrap, and stir it on a magnetic stirrer until the sawdust in the solid-liquid mixture completely turns white; (2) centrifuging the solid-liquid mixture obtained in step (1), taking out the lower layer of colloid, and rinsing it in deionized water, centrifuging the mixture again, taking out the lower layer of colloid, and rinsing it in deionized water three times to remove residual chemicals, thereby obtaining a white colloid, namely cellulose; (3) freeze-drying the colloidal cellulose obtained in step (2), and then vacuum drying to obtain freeze-dried cellulose, dividing the freeze-dried cellulose into small pieces, soaking them in deionized water, and using an ultrasonic cell crusher to break up the resulting solid-liquid mixture until the freeze-dried cellulose is completely broken to form a milky white suspension; (4) stirring the milky white suspension obtained in step (3), pouring it into a polytetrafluoroethylene liner, placing it into a high-pressure reactor, reacting it in a vacuum drying oven using a hydrothermal method, and taking it out after the reactor is cooled; (5) Centrifuging the solid-liquid mixture obtained in step (4), taking out the supernatant and filtering it, and freeze-drying the filtrate to obtain a viscous solid. Then dissolving the viscous solid in water, and repeatedly centrifuging and filtering it several times to obtain a dark brown viscous solid, i.e., a carbon dot solid; (6) adding polyvinyl alcohol solid particles into deionized water, stirring and heating until completely dissolved, and then cooling to room temperature to obtain a polyvinyl alcohol (PVA) solution; (7) Dissolving the carbon dot solid obtained in step (5) in deionized water to obtain a carbon dot solution, mixing the carbon dot solution with the polyvinyl alcohol solution obtained in step (6), adding the polyvinyl alcohol solution to the mixed solution until the total volume of the mixed solution is 20 ml, treating the mixed solution with an ultrasonic cell crusher, and then drying the mixed solution in a vacuum drying oven to obtain a light brown luminescent film.

2. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (1), the mass of sawdust is weighed to be 9 g, the concentration of the sodium hypochlorite solution is 4.8 wt %, 200 ml of the sodium hypochlorite solution is weighed, and the stirring time of the magnetic stirrer is about 60 min.

3. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (2), the centrifugal speed of the centrifuge is 10000 r / min and the centrifugal time is 5 min.

4. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (3), the freeze drying time is about 4 hours, the vacuum drying time is about 20 hours, the freeze-dried cellulose mass is weighed to be 0.171 g, 60 ml of deionized water is weighed, the power of the ultrasonic cell crusher is set to 45%, the operation time is 1.5 seconds, and the interval time is 2 seconds.

5. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (4), the speed of the magnetic stirrer can be controlled below 300 r / min, 100 ml of the polytetrafluoroethylene liner is taken, and the temperature in the vacuum drying oven is adjusted to 200° C. for 720 min.

6. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (5), the centrifugal speed of the centrifuge is 10000 r / min, the centrifugal time is 5 min, and a 0.22 μm microfiltration membrane is used for filtration.

7. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (6), 40 g of polyvinyl alcohol solid particles and 460 ml of deionized water are weighed, the stirring speed of the thermomagnetic stirrer is 200 r / min, and the heating temperature does not exceed 80°C.

8. The method for preparing sawdust-based carbon dots and luminescent films thereof according to claim 1, characterized in that: In step (7), the mass volume ratio of carbon dot solid and deionized water is 5:1, the concentration of the polyvinyl alcohol solution is 8wt%, the polyvinyl alcohol is selected as 1788 low-viscosity type, the degree of alcoholysis is 87.0-89.0%, the power of the ultrasonic cell crusher is set to 45%, the operation is 1.5s, the interval is 2s, and the duration is 3min. The temperature of the vacuum drying oven is adjusted to 60°C, and the vacuum drying time is about 7h.

9. Carbon dots prepared according to the method according to any one of claims 1 to 8 and a luminescent film thereof.

Citation Information

Patent Citations

  • Synthesis and application of photoluminescent lignin-based carbon quantum dot

    CN110436439A

  • Biomass carbon dot / wood composite photocatalytic material and preparation method and application thereof

    CN112169810A

  • Preparation method of multicolor fluorescent transparent wood based on carbon quantum dots and transparent wood

    CN113459230A

  • Rapid and simple preparation method of lignin-based carbon quantum dots with high quantum yield

    CN113620274A

  • Preparation method of cellulose-based carbon dots and application in field of blue light resistance

    CN113861970A